Microwave-assisted hydrothermal extraction of natural malic acid for the synthesis of low transition temperature mixtures. (1st February 2016) - Yiin, Chung Loong; Yusup, Suzana; Quitain, Armando T.; Sasaki, Mitsuru; Uemura, Yoshimitsu; Kida, Tetsuya
Abstract: This work describes the utilization of microwave hydrothermal extracted malic acid from cactus, lophatherum herb, papaya and Luffa cylindrica as hydrogen bond donor for the synthesis of natural low transition temperature mixtures (LTTMs) with sucrose as hydrogen bond acceptor. The effects of parameters including reaction temperature, extraction time, mass of sample and oxidant, H2 O2 were discussed. The saturation equation was used to fit with the experimental data, observing only a slight loss of the goodness of fit. The optimum conditions for microwave hydrothermal extraction were found to be at 1 g of sample, 200 °C and 45 min in the presence of hydrogen peroxide (H2 O2 ) as oxidant. Consequently, the proposed method was successfully applied to extract malic acid from plants and fruits for the synthesis of LTTMs. The LTTMs prepared from the extracted malic acid have identical physicochemical properties with the LTTMs derived from commercial malic acid due to the existence of hydrogen bond and the ability to dissolve lignin. Graphical abstract: Highlights: Malic acid was extracted through microwave-assisted hydrothermal technique. Saturation equation was used for optimization and kinetic modelling of data. Green solvents were synthesized from extracted malic acid as hydrogen bond donor. Hydrogen bonding of green solvents was evidenced by the shifts in peaks. The green solvents showed promising lignin solubility.